Satellite-derived prediction on habitat modelling of skipjack tuna (Katsuwonus pelamis) in the Makassar Strait, Indonesia - Mega L. Syamsuddin; Subiyanto Subiyanto; Tonny Bratasena; Fadli Syamsudin; Noir P. Purba; Yudi Nurul Ihsan; Ajeng R. Puspita; Mukti Zainuddin; Nofrita Nofrita (Geocarto International)
The Makassar Strait is one of the Indonesian Throughflow (ITF) branches that transports warm water masses from the Pacific Ocean to the Indian Ocean. These water masses have a significant impact on oceanographic parameters, which in turn affects the skipjack tuna distribution. Satellite-derived oceanographic factors from January 2015 to December 2020 included sea surface temperature (SST), chlorophyll-a, salinity, sea surface height (SSH), surface current, and surface wind are used to predict the potential habitat of skipjack tuna (Katsuwonus pelamis) in the Makassar Strait using the maximum entropy (MaxEnt) model. The SSH was the most important oceanographic variable affecting the skipjack tuna catch, contributing 49.7% to the model gain. An increasing skipjack tuna catch was observed within the following oceanographic variable ranges: 0.48–0.58 m of SSH, 34–35 ppt of salinity, 0.1–1.2 m/s of surface current, 29–30 °C of SST, 5–6 m/s of surface wind, and 0.1–0.5 mg/l of chlorophyll-a concentrations.